Kajian aliran tepu persimpangan berlampu isyarat di Lembah Kelang - Ismail Abdul Rahman, (1992)
This research is aimed at studying factors that influence saturation flow at signalized intersections in Kelang Valley. In this study local drivers and vehicles characteristics, geometric design and traffic regulations are taken into considerations. The results show that the relationship introduced by Webster and Cohbe, gives an underestimated value of saturation flow at any given approach. Comparison between three most frequently used models i.e. Webster and Cohhe, Akcelik and Ellson and Kimber shows that Kimber model gives a more realistic estimation of the effects of turning radius magnitude and percentage of turning vehicles on the local saturation flow. Passenger-car unit values recommended by Webster and Cohbe give a close estimation to real conditions for all types of vehicles except for buses